Innovations and development of sustainable personal protective equipment: a path to a greener future - Linxiang Lyu; Monisha Bagchi; Nektaria Markoglou; Chunjiang An (Environmental Systems Research, 2024)
Abstract The unprecedented surge in the demand for personal protective equipment (PPE) worldwide during the covid pandemic resulted in a significant increase in PPE consumption and subsequent waste generation. Despite the importance of PPE, its widespread usage and disposal have sparked worries about the environmental impact and its long-term sustainability. The increasing awareness of environmental challenges, resource scarcity, and the urgent need to mitigate climate change necessitates a paradigm shift in the product design, manufacturing process, and waste management of PPE. To address these challenges and have a sustainable PPE future, the development of degradable polymers and natural fibers offers a promising alternative to traditional plastics. Additionally, recycling and upcycling methods can convert the waste into valuable alternate products or energy sources, thereby reducing their environmental impact. Better waste management systems, comprehensive policy frameworks, and international collaborations are essential for the effective PPE waste management and the promotion of sustainable practices. Despite the challenges, collaborative efforts across governments, manufacturers, research institutions, and waste management authorities are crucial for transitioning to a more sustainable PPE industry and a circular economy, ultimately benefiting both the environment and society.